PENGARUH ETIKA AUDITOR, MOTIVASI AUDITOR, LOCUS OF CONTROL TERHADAP KUALITAS AUDIT DENGAN SKEPTISME PROFESIONAL AUDITOR SEBAGAI VARIABEL INTERVENING - Chriscarol Antami Parluhutan (2021)
Good audit quality is needed so that financial statements can be useful for the community as a basis for making decisions. Reported from the tirto.id page (2/21), the Corruption Eradication Commission (KPK) named a member of the Supreme Audit Agency (BPK) as a suspect in a drinking water bribery case because an abnormal value was found in the financial statements and in 2017 the BPK auditor was caught in the act of buying and selling opinion on the financial statements of the Ministry of Villages. This can be indicated by the existence of fraud in the audit results which makes the quality of the audit doubtful. This research was determine the effect of auditor ethics, auditor motivation, locus of control on audit quality with auditor professional skepticism as an intervening variable. The sample used in this reaserch amounted to 59 samples who came from auditors AKN V and VI BPK RI with a questionnaire instrument. The analysis technique used is Structural Equation Modelling (SEM), using the Smart Partial Least Square version 3.0. The results of this study indicate that auditor ethics, auditor motivation, and locus of control have a significant effect on audit quality. Auditor professional skepticism has no significant effect on audit quality. And auditors' professional skepticism cannot mediate the relationship between auditor ethics and audit quality.